Brown Rice Consumption Effect on Blood Sugar Levels in Type-2 Diabetes Bibliometric Analysis - Zilva Karimah Azahra (Jurnal Teknik Industri, Sistem Informasi dan Teknik Informatika, 2023)
The bibliometric analysis aimed to explore brown rice consumption's impact on blood sugar levels, particularly for type 2 diabetes patients. It utilized Publish or Perish software and Google Scholar database alongside Microsoft Excel 2016 and VOSviewer for data visualization. Using keywords like "brown rice," "blood sugar levels," and "type-2 diabetes," the analysis identified influential researchers like Zhang, Y, and Liu, L. Findings revealed Elsevier as the leading publisher, with a notable citation count of 703. The prevalent terms in the research encompassed "rice," "brown rice," and "health benefits," forming 10 distinct clusters. This research theme, crucial for health, is projected to progress further, emphasizing the significance of carbohydrates in health and well-being. The analysis showcased trends, influential contributors, and prevalent topics, underscoring brown rice's importance in managing blood sugar levels, especially for individuals with type 2 diabetes.